A lithium ion battery model considering state-of-charge and battery current. Issue 1 (2nd January 2016) - Hsieh, Yao-Ching; Liao, Chien-Nen; Chen, Jui-Chi; You, Zhen-Hou
Abstract: In this paper, an electric circuit model for lithium-ion batteries is proposed for predicting the over-voltage transients after discharging or charging. Primary factors, such as state-of-charge ( SOC ), and battery current are separately experimented to examine their impacts. Kalman filter algorithm is applied to analyze the long-time recorded data, so as to identify the over-potential features during each different SOC stage. On monitoring battery current and voltage, the model is capable of predicting the over-voltage dynamics. Finally, experiments are carried out to verify the model to test the feasibility of the battery model.